The Dynamics of Annonaceae Plants Collection and Its Conservation Efforts in Purwodadi Botanic Garden - Dewi Ayu Lestari; Ahmad Masrum (Biosaintifika: Journal of Biology & Biology Education, 2020)
Plant species of Annonaceae family were collected in Purwodadi Botanic Garden (PBG) needs ex-situ conservation efforts to prevent threat of extinction. Annonaceae plants collection in PBG have experienced dynamics over the past of 12 years which affect to diversity and conservation efforts. This study aimed to determine the dynamics or development of Annonaceae plants collection in PBG for the past of 12 years and how their conservation efforts. The methods were used are primary and secondary data collections from Registration Unit, measurement of stem diameter, plant height, branch-free stem height (BFS) of Annonaceae plants collection and microclimatic data (temperature, humidity, soil pH and light intensity) in each block of Annonaceae plants collection. Data were analyzed descriptively and by Principal Component Analysis using the statistical program PAST 4.0. The Annonaceae plant collections in PBG have fluctuated in the number of plants, genera, species, specimens and unidentified species with the addition of 28, 10, 6, 58, and 7 plants respectively. There were also 81 times of species identity changes. Annonaceae plant collections in PBG was able to well adapt and develop based on the average of stem diameter and BFS, with humidity and light intensity became the most influential environmental factors for plant growth. The management of Annonaceae plant collections in PBG consisted of the maintenance activities and studies to support the conservation. By regulating and manipulating of humidity and light intensity in Annonaceae plant collections, plant growth will increase and well maintenance. Management efforts can be planned and developed properly by knowing the dynamics of plant collections.